Crop water stress index assessment of safflower (Carthamus tinctorius L.) under limited water conditions - Hüseyin Tevfik Gültaş (Scientia Agricola)
ABSTRACT To ensure the sustainability of agriculture and the production of safe food, supplementary irrigation is required for crops that are primarily rainfed, particularly in arid conditions. This study aimed to determine the water stress response of safflower (Carthamus tinctorius L.) under limited water conditions and to establish the crop water stress index (CWSI) as a basis for crop-based irrigation scheduling. Irrigation applications were conducted using the line-source sprinkler irrigation method to create three constraints (35, 75, and 100 % of the water requirement) and a rainfed condition (control plot) under different crop growth periods. The main plots consisted of three growth periods of safflower and only one supplementary irrigation during the vegetative, flowering, and ripening periods. The highest yield was obtained at 3.06 and 3.42 t ha–1 for 2019 and 2021, respectively, in the plot that was irrigated in each period during the growing season. The irrigation water (I) and water use efficiency (WUE) were 0.42 and 0.51 kg m–3 in the first year, and 0.47 and 0.59 kg m–3 in the second year, respectively, for the subject fully irrigated throughout the season. The upper base value, which can be utilized in calculations of the CWSI, was determined to be approximately 14.50. The lower base equation was obtained as Y = −4.9428 (VPD) + 19.121 at a statistical significance level of 1 % where Y is yield and VPD is vapor pressure deficit. The CWSI values calculated for each treatment ranged between −0.25 and 1.45. The threshold value at which irrigation should commence was determined to be 0.63, and it will serve as a valuable reference data source for irrigation scheduling.